Long term care for elderly in USA - Klepacz, Lidia; Załuska, Wojciech; Książek, Andrzej (Polish Journal of Public Health, 2009)
The main purpose of this article is to introduce physicians and health care providers in Poland to American system that was designed to care for elderly in the different settings. During the 20th century the number of people under 65 in US has tripled. It is predicted that between now and the year 2050, the number of elderly will double and will reach 80 million in USA alone. This tendency will be seen all over the World and it will become a global health and management problem. With the tremendous advances in medical research and technology, development of new diagnostic procedures and medications, people will live longer, therefore elderly population will need more services and long term care options.